VD_FINDINFO HC / 2020 / 926 vom 9. Dezember 2020 - VD Tribunal cantonal (2020)
SUCCESSION, DOMICILE, COMPÉTENCE, CAMEROUN, AUTORITÉ ÉTRANGÈRE, ADMISSION DE LA DEMANDE, DÉCISION DE RENVOI | 29 al. 2 Cst., 87 LDIP